Assessment of sustainable transport policies with an energy-economy-environment model - Zachariadis, Theodoros (My University, 2005)
Sustainable development is widely accepted as an important ingredient in formulating long-term strategies, and transport is recognised as a priority area in sustainability discussions. Because of the inherent complexity of this sector in comparison to most other branches of economic activity due to the millions of travellers involved, policy measures often have to be taken at local scale and respecting local particularities. In order to respond to requirements of a European research study, an appropriate assessment tool had to be used. Based on the experience collected so far, a new model was developed, which is described in this paper. The model covers the whole transport sector (road and rail transport, inland shipping and aviation) in the 15 countries that were EU Member States in the beginning of 2004. It attempts to bridge the gap between top-down energy-economy models, which address the transport sector in an aggregate fashion, and bottom-up technological models, which provide sufficient technological coverage but often cannot simulate the effect of behavioural changes induced by changing costs and income. It covers the major sustainability issues associated with the transport sector, i.e. emissions of air pollutants and greenhouse gases, energy intensity, congestion, road accidents and noise. Its underlying database is consistent with those of EU institutions such as the European statistical service (Eurostat), the European Commission and the European Environment Agency, a feature that ensures acceptance by policy makers at national and international level. Starting from a simulation of the economic behaviour of consumers and producers within a microeconomic optimisation framework and the resulting calculation of the modal split, the allocation of the vehicle stock into vintages and technological groups is modelled. In a third step, a technology-oriented algorithm, which incorporates the relevant state-of-the-art knowledge in Europe, calculates emissions of air pollutants and greenhouse gases as well as appropriate indicators for traffic congestion, noise and road accidents. The paper describes briefly the methodological approach, which has been presented elsewhere. Its main focus is the presentation of assumptions and results of several alternative scenario runs that attempt to simulate individual policies aiming to promote sustainable transport. Examples of such policies are: urban road pricing, early implementation of stricter vehicle emission standards, road infrastructure investments as well as economic subsidies for encouraging public transport, using alternative fuels and scrapping old cars. A major conclusion drawn from the results is that individual policy measures cannot respond sufficiently to the diverse sustainability concerns associated with transportation. Therefore, a suite of policies combining promotion of advanced 'conventional' technologies and alternative fuels with economic and regulatory interventions to reduce demand for transport would be most appropriate.
Keywords: Optimisation; Noise; Accidents; Congestion; Emissions; Microeconomics